Copper-catalyzed aliphatic C-H oxidation with Amidines and Amidoximes - Chen, Hui (2016)
This thes is describes studies on copper-catalyzed aliphatic C-H oxidation (oxygenation and amination) of amidines and amidoximes for the synthesis of highly functionalized azaheterocycles. The key feature of these transformations involves remote H-radical shift of an amidinyl radical I generated by single-electron-oxidation of amidine by higher valent [Cun+1] species to form a C-radical II. The resulting C-radical II is further functionalized to afford azaheterocycles (Scheme I). Chapter 2 describes Cu-catalyzed aerobic C-H oxygenation of N-alkylamidines for the construction of dihydrooxazoles. In this process, the C-radical II generated by 1,5-H radical shift of the amidinyl radical I is oxygenated and subsequently cyclized to form a dihydrooxazole (Scheme 2A). This C-H oxygenation strategy is further applied to the synthesis of 4H-I ,3-benzoxazines via 1,6-H radical shift. It could be speculated that after a 1,5-H radical shift, the resulting C-radical II could be aminated by the amidine nitrogen in the presence of another type of oxidant instead of using molecular oxygen . The author has developed Cu-catalyzed PhI(OAc)2-mediated aliphatic C-H amination of N-alkylamidines for the synthesis of dihydroimidazoles (Scheme 2B), which is described in Chapter 3. Chapter 4 describes Cu(I)-catalyzed Sp3 C-H amination with amidoximes, where the N-O bond of amidoximes serves as an internal oxidant. The reaction mechanism could be characterized as a redox-neutral radical pathway including a Cu(I)-Cu(II) redox catalytic cycle (Scheme 2C). This strategy has been further extended for the synthesis of quinazolinones from N-benzoylamidoximes via Sp2 C-H amination (Scheme 2D).